Risk factors associated with infant mortality due to malnutrition. Benguela General Hospital, Angola: Factores de riesgo asociados a la mortalidad infantil por desnutrición. Hospital General de Benguela, Angola - Gómez-Martínez, Freddy (2022)
Introduction: Child malnutrition is a major challenge for Angola. Objective: to identify factors associated with mortality due to child malnutrition in the Provincial Hospital of Benguela. Materials and methods: Case-control, observational and analytical study. The case group, made up of 51 children who died of malnutrition between May 2019 and May 2020, and the control group, made up of 102 living malnourished children. The matching was carried out according to the following criteria: diagnosis of malnutrition, age group, sex and origin. Medical records were the source of information. The X2 test made it possible to determine the association between the study variable and the rest, while the OR classified them as risky or protective, with 95% confidence. Results: The mean age of the case group was 16.6 months, 51% were infants with a predominance of females (53.9%). The risk of death due to malnutrition increased by 7.2 and 4.5 times in the clinical variables not applying preventive antibiotic therapy or blood transfusion, respectively, and mucocutaneous pallor by 5.1 times. With the same impact, but in non-clinical variables, difficulty breastfeeding (4 times), presence of younger siblings (3.4 times), not breastfeeding (2.5 times) and low birth weight (4.5 times). The protective variables for the risk of dying from malnutrition were vaccination, institutional delivery and term. Conclusions: There are clinical and non-clinical factors that increase the risk of dying from malnutrition while others act as protectors. Their identification will facilitate the implementation of prevention measures. Keywords: Child Mortality, Malnutrition, Risk Factors (Source: MeSH, NLM).